Synthesis of precursor of anti-inflammatory agents by using highly reactive zinc - Abdul Jalil, Aishah (Malaysian Medical Association, 2004)

(untitled)
Highly reactive zinc was prepared by electrolysis of a N,N-dimethylformamide (DMF) solution containing naphthalene and a supporting electrolyte in a one-compartment cell fitted with a platinum cathode and a zinc anode. This highly reactive electrogenerated zinc (EGZn/Naph) was used for transformation of ethyl 2-bromoacrylate into the corresponding organozinc compound, which can not be achieved by the use of usual zinc metals. Reaction of the organozinc compound thus prepared various aryl halides in the presence of 5 % or palladium catalyst gave the corresponding cross-coupling products in high yields. These cross-coupling reactions were successfully applied to a synthesis of, the precursor of anti-inflammatory agents such as ibuprofen, naproxen, cicloprofen and suprofen.